2022
DOI: 10.31223/x57p74
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fully distributed rainfall-runoff modeling using spatial-temporal graph neural network

Abstract: Recent studies using latest deep learning algorithms such as LSTM (Long Short-Term Memory) have shown great promise in time-series modeling. There are many studies focusing on the watershed-scale rainfall-runoff modeling or streamflow forecasting, often considering a single watershed with limited generalization capabilities. To improve the model performance, several studies explored an integrated approach by decomposing a large watershed into multiple sub-watersheds with semi-distributed structure. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…On the other hand, our framework and models were developed for forecasting at the watershed level, and we neglected the geographical distribution of rainfall. Several simulation experiments involving graph neural networks have been conducted (Jia et al, 2021;Xiang et al, 2022), and that could be addressed in future studies. We recommended updating the deep learning model continuously with the most recent data in our framework as a potential improvement step for prediction.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our framework and models were developed for forecasting at the watershed level, and we neglected the geographical distribution of rainfall. Several simulation experiments involving graph neural networks have been conducted (Jia et al, 2021;Xiang et al, 2022), and that could be addressed in future studies. We recommended updating the deep learning model continuously with the most recent data in our framework as a potential improvement step for prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Utilization of graph neural networks in hydrological context has been appealing to domain scientists lately. While Sit et al [36] forecasted hourly stream ow for a basin in Iowa using upstream information, Xiang and Demir [37] showed that a similar approach could be used to generalize forecasts for the whole state. In a similar approach, Jia et al [38] showed that recurrent graph models outperformed LSTM networks for both water ow and temperature in a transfer learning approach.…”
Section: Graph Neural Network (Gnns) In Hydrologymentioning
confidence: 99%
“…However, advancements in artificial intelligence (AI) coupled with the increasing capabilities of graphics processing units (GPUs) have opened up new possibilities and accelerated the progress of deep learning techniques, which has led to the widespread usage of these techniques in streamflow forecasting as well (Sit et al, 2022a). Out of various neural network architectures explored for streamflow forecasting (Sit et al, 2021a;Xiang and Demir, 2022b;Chen et al, 2023), Recurrent Neural Networks (RNNs), especially the Long Short-Term Memory (LSTM) neural network and Gated Recurrent Units (GRUs), have emerged as the most extensively studied and researched models in this domain. Kratzert et al (2018) applied an LSTM model to predict daily runoff, incorporating meteorological observations, and demonstrated that the LSTM model outperformed a wellestablished physical model in their study area.…”
Section: Introductionmentioning
confidence: 99%